Epigenetic regulation and the variability of gene expression - Choi, Jung Kyoon; Kim, Young-Joon (Nature genetics, 2008)
We characterized the genetic variability of gene expression in terms of trans and cis variability for each yeast transcript. Genes that are highly regulated by nucleosomes showed a high degree of trans variability. From the expression profiles of mutants for various chromatin modifiers, we found that trans -variable genes are distinctly regulated at the chromatin level. The effect of chromatin regulators was highly significant, even when compared with that of transcription factors. The DNA-binding activities of transcription factors had a low influence on trans variability. In the case of the basal transcription factor TBP and TBP-associated factor TAF1, expression variability was coupled with the histone acetyltransferase activities of TAF1 and other factors, rather than with the binding of TBP to DNA. Additionally, we found that the correlation of TATA-box presence and expression variability could be explained in terms of chromatin regulation. The lack of activating histone modifications may subject TATA-containing promoters to chromatin regulation processes. Our results propose that epigenetic regulation has a central role in the variation and evolution of gene expression.